Optical clearing in collagen- and proteoglycan-rich osteochondral tissues. Issue 3 (March 2015) - Neu, C.P.; Novak, T.; Gilliland, K.F.; Marshall, P.; Calve, S.
Summary: Objective: Recent developments in optical clearing and microscopy technology have enabled the imaging of intact tissues at the millimeter scale to characterize cells via fluorescence labeling. While these techniques have facilitated the three-dimensional (3D) cellular characterization within brain and heart, study of dense connective tissues of the musculoskeletal system have been largely unexplored. Here, we quantify how optical clearing impacted the cell and tissue morphology of collagen-, proteoglycan-, and mineral-rich cartilage and bone from the articulating knee joint. Methods: Water-based fructose solutions were used for optical clearing of bovine osteochondral tissues, followed by imaging with transmission and confocal microscopy. To confirm preservation of tissue structure during the clearing process, samples were mechanically tested in unconfined compression and visualized by cryo-SEM. Results: Optical clearing enhanced light transmission through cartilage, but not subchondral bone regions. Fluorescent staining and immunolabeling was preserved through sample preparations, enabling imaging to cartilage depths five times deeper than previously reported, limited only by the working distance of the microscope objective. Chondrocyte volume remained unchanged in response to, and upon the reversal, of clearing. Equilibrium modulus increased in cleared samples, and was attributed to exchange of interstitial fluid with the more viscous fructose solution, but returned to control levels upon unclearing. In addition, cryo-SEM-based analysis of cartilage showed no ultrastructural changes. Conclusion: We anticipate large-scale microscopy of diverse connective tissues will enable the study of intact, 3D interfaces (e.g., osteochondral) and cellular connectivity as a function of development, disease, and regeneration, which have been previously hindered by specimen opacity.